Incidence and Survival of Multiple Primary Cancers in US Women With a Gynecologic Cancer - Corey, Logan; Ruterbusch, Julie; Shore, Ron; Ayoola-Adeola, Martins; Baracy, Michael; Vezina, Alex; Winer, Ira (Frontiers in Oncology, 2022)
Objectives To evaluate risk of a second cancer and associated survival times in United States women with diagnosis of cancer. Methods The Surveillance Epidemiology and End Results (SEER) database was queried for 2 cohorts of women aged 18 - 89 with either an index gynecologic or non-gynecologic cancer diagnosed between 1992 – 2017. Index cases were followed to determine if a second primary cancer was subsequently diagnosed; defined according to SEER multiple primary and histology coding rules. Standard Incident Ratios (SIR) and latency intervals between index diagnosis and second primary diagnosis were evaluated. Among those who developed a second primary cancer, median survival times from diagnosis of second primary cancer were also calculated. Results Between 1992 – 2017, 227,313 US women were diagnosed with an index gynecological cancer and 1,483,016 were diagnosed with an index non-gynecologic cancer. Among patients with index gynecologic cancer, 7.78% developed a non-gynecologic subsequent primary cancer. The risk of developing any non-gynecologic cancer following an index gynecologic cancer was higher than the risk in the general population (SIR 1.05, 95% CI 1.04 - 1.07). Organs especially at risk were Thyroid (SIR 1.45), Colon and Rectum (SIR 1.23), and Urinary System (SIR 1.33). Among women diagnosed with an index non-gynecologic cancer, 0.99% were diagnosed with a subsequent gynecologic cancer. The risk of developing a gynecologic cancer following a non-gynecologic cancer was also elevated compared to the average risk of the general population (SIR 1.05, 1.03 - 1.07), with uterine cancer having the highest SIR of 1.13. Conclusion The risk of a developing a second primary cancer and the corresponding survival time is based on the order and site of the index and subsequent cancer. Surveillance guidelines should be examined further to optimize survivorship programs.